2008
DOI: 10.1089/hum.2008.064
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia-Induced Targeting of Thermosensitive Gene Carriers to Tumors

Abstract: Locoregional hyperthermia (HT) can be used for site-directed activation of macromolecular drug delivery systems. We have developed a gene delivery system based on thermosensitive block copolymers (TSCs) with a phase transition temperature of 42 degrees C [Zintchenko, A., Ogris, M., and Wagner, E. (2006). Bioconjug. Chem. 17, 766-772], in which the statistical copolymer of vinylpyrrolidinone and N-isopropylacryamide is grafted on polyethylenimine (PEI). Here we applied polyplexes consisting of plasmid DNA and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…3). 28 26 Changes in DNA-binding affinity of the sets of block co-polymers were observed across the temperature ranges in gel retardation assays, while NMR and neutron scattering studies further supported a mechanism in which supramolecular architectures of the polymers changed across LCST.…”
Section: Martyn C Daviesmentioning
confidence: 90%
“…3). 28 26 Changes in DNA-binding affinity of the sets of block co-polymers were observed across the temperature ranges in gel retardation assays, while NMR and neutron scattering studies further supported a mechanism in which supramolecular architectures of the polymers changed across LCST.…”
Section: Martyn C Daviesmentioning
confidence: 90%
“…In recent years, a number of other thermoresponsive cationic polymers were prepared and studied as gene carriers. 183 This work implies that other nucleic acids such as siRNA can also be sitespecifically delivered by a combination of hyperthermia and thermoresponsive polymers. 178 Park et al reported another temperature-sensitive gene delivery system.…”
Section: Thermoresponsive Systemsmentioning
confidence: 99%
“…The poly(NIPAM-VP)-block-PEI delivered a 10-fold higher amount of plasmid DNA to tumor tissue under the hyperthermia condition than branched PEI (25 kDa) in a mouse model. [70] Moreover, hyperthermia induced gene delivery by poly(NIPAM-VP)-block-PEI, which significantly reduced non-specific delivery of plasmid DNA to normal tissues such as lung, heart, liver and kidney.…”
Section: Targeted Delivery Of Nucleic Acid Drugs Via Environmentally mentioning
confidence: 99%